Fuzzy logic based control for IPFC for damping low frequency oscillations in multimachine power system - Parimi, A.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
Mitigation of power system oscillations, within the frequency range of 0.1 to 2 Hz, is the problem of concern in the power industry as these oscillations, when exhibiting poor damping; affect the transmission line power transfer capability and power system stability. These low frequency oscillations greatly restrict power system operations and, in some cases, can also lead to widespread system disturbances. In this context, the Flexible AC Transmission System (FACTS) device, Interline Power Flow Controller (IPFC) employed to improve the transmission capability can be additionally utilized for damping control of power system oscillations. A fuzzy logic based IPFC damping controller is designed and compared with conventional damping controller to mitigate the low frequency oscillations for the mulitmachine power system. Case studies on three-machine nine-bus (IEEE WSCC) mulitmachine power system have been carried out in Matlab Simulink. The nonlinear simulation studies of the investigations conducted on the Multi-machine power systems installed with IPFC demonstrate that the control designs are effective in damping the power system oscillations. © 2015 IEEE.